SEAWATER PH CONTROL ON THE BORON ISOTOPIC COMPOSITION OF CALCITE: EVIDENCE FROM INORGANIC CALCITE PRECIPITATION EXPERIMENTS - Sanyal A.; Nugent M.; Reeder R.J.; Bijma J. (My University, 2000)
Experiments involving boron co-precipitation with calcite have been carried out inorganically under controlled pH conditions (7.9 +/- 0.05, 8.3 +/- 0.05 and 8.6 +/- 0.05) to determine the dependence of the boron isotopic composition (δ11B) of calcite on the pH of seawater. Another purpose of these experiments was to estimate the magnitude of the biogenic influence on the δ11B value of foraminifera by comparing their boron isotopic composition with that of the inorganic calcite over a common pH range. The results show a clear relationship between δ11B of inorganic calcite and the pH of artificial seawater. The variation of boron isotopic fractionation between seawater and calcite with pH, estimated from these experiments, is similar to that estimated for cultured O. universa and the theoretically predicted trend. The results also support the hypothesis that B(OH)4- is the dominant species incorporated into the calcite structure. However, the boron isotopic fractionation between seawater and inorganic calcite is lower than that estimated for O. universa indicating the presence of a biogenic effect on the boron isotopic composition at least of this species of foraminifera. Most importantly, the results imply that in spite of a small biogenic influence on the boron isotopic composition of foraminifera, the variation in δ11B of foraminiferal shells with pH (at least for O. universa) is comparable to that for inorganic calcite, supporting the potential of this isotopic signature in foraminifera as a reliable paleo pH proxy.